Chapter 5: Transplant Production - Kent Cushman (EDIS)
Vegetable transplants are affected by many factors, but the most important are water, temperature, fertilization, sunlight, cell size, and length of stay in the greenhouse (Fig. 5-1). These factors must be managed to produce a product that is acceptable to the customer (Fig. 5-2). This document is HS714, one of a series of the Horticultural Sciences Department, UF/IFAS Extension. Original publication date June 1995. Revised November 2006.